A conglomerate model for identification of the interaction between job satisfaction and job performance in a service institution - a context bound approach. (2015) - Punniyamoorthy, Murugesan; Lavanya, Vilvanathan
Job satisfaction is a complex, multifaceted concept influenced by both positive and negative experiences at workplace. This study is a context based study, aimed at understanding the mindset of the professors in a government institution. To accomplish the mentioned objective, Oldham and Hackman's job characteristic model and Bagozzi reciprocal model have been adopted in this study and a causal model has been formed. It was observed from the results of the model that majority of the faculty felt stronger about their sense of work responsibility due to the autonomy experienced in doing the job, which also provided them a sense of contentment. On the contrary, they were uncertain about the meaningfulness of their jobs while task identity and task significance were assessed. Faculty also indicated a strong desire to experience stimulating work and the opportunity to exercise creativity and self-determining thought. Despite appreciating the feedback received from colleagues the faculty members were least satisfied with pay and overall satisfaction with the job. The study thus unravels the knot whether job satisfaction influences job performance or vice-versa.